2014
DOI: 10.13102/sociobiology.v61i2.218-224
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Status of the social wasp Polistes versicolor (Hymenoptera, Vespidae)

Abstract: Introduction An important feature for the ecological success of social insects is the division of labor among individuals in their colonies (Wilson, 1985). For this reason, many investigators have devoted their efforts to elucidate the parameters that determine this division, especially the distinction and determination of the caste (Robinson, 1992; O'Donnell, 1995; O'Donnell, 1998). The subfamily Polistinae has characteristics that are important to understand how the social behavior has evolved in the wasps (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…(2014) did not find any morphometric differences between the queen and worker castes of this species when they assessed females of non-parasitized colonies. The absence of morphometric differences between the castes has also been reported in Polistes versicolor (Torres et al 2014).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…(2014) did not find any morphometric differences between the queen and worker castes of this species when they assessed females of non-parasitized colonies. The absence of morphometric differences between the castes has also been reported in Polistes versicolor (Torres et al 2014).…”
Section: Discussionsupporting
confidence: 58%
“…1999; Sledge et al . 2001; Heinze et al 2002; Kelstrup et al 2014; Soares et al 2014; Torres et al 2014), which consequently determines its role in the colony. The effect of the endoparasite in altering the chemical signature in P. dominula was reported by Dapporto et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, insemination also leads to significant differences between linear alkanes composition of females (Fig 3). Torres et al (2014) studying the relationship between cuticular chemical profile and physiological condition of P. versicolor females, found correlation between ovarian development and spermatheca condition. Soares et al (2014) also found similar results studying colonies of Polistes ferreri Saussure 1853.…”
Section: Discussionmentioning
confidence: 99%
“…This chemical profile is specific to each individual, signaling, for example, the role of each worker within the colony (Ferreira-Caliman et al, 2010;Kather et al, 2011). Specifically, alpha females responsible for reproduction possess cuticular chemical compounds different from those found in workers, as described in studies of the wasp species Polistes versicolor (Olivier) (Torres et al, 2014) and Polistes ferreri (Sassure) (Soares et al, 2014).…”
Section: Introductionmentioning
confidence: 99%